SOME ADDITIONAL NOTES ON THE PRECEDING,"REPORT ON A SMALL COLLECTION OF PARASITIC HYMENOPTERA FROM JAVA AND SUMATRA BY A. B. GAHAN" AND ON "DESCRIPTIONS OF JAVANESE BRACONIDAE RECEIVED FROM Mr. S. LEEFMANS BY S. A. ROHWER" - S. LEEFMANS (Treubia, 1923)
-